Production and efficacy of a low-cost recombinant pneumococcal protein polysaccharide conjugate vaccine. Issue 26 (18th June 2018) - Herbert, Jenny A.; Kay, Emily J.; Faustini, Sian E.; Richter, Alex; Abouelhadid, Sherif; Cuccui, Jon; Wren, Brendan; Mitchell, Timothy J.
Highlights: Pneumococcal glycoconjugate vaccines produced in E. coli are protective in mice. Protection correlates with opsonic antibody levels. This is a cheaper way to produce conjugate vaccines. Abstract: Streptococcus pneumoniae is the leading cause of bacterial pneumonia. Although this is a vaccine preventable disease, S. pneumoniae still causes over 1 million deaths per year, mainly in children under the age of five. The biggest disease burden is in the developing world, which is mainly due to unavailability of vaccines due to their high costs. Protein polysaccharide conjugate vaccines are given routinely in the developed world to children to induce a protective antibody response against S. pneumoniae . One of these vaccines is Prevnar13, which targets 13 of the 95 known capsular types. Current vaccine production requires growth of large amounts of the 13 serotypes, and isolation of the capsular polysaccharide that is then chemically coupled to a protein, such as the diphtheria toxoid CRM197, in a multistep expensive procedure. In this study, we design, purify and produce novel recombinant pneumococcal protein polysaccharide conjugate vaccines in Escherichia coli, which act as mini factories for the low-cost production of conjugate vaccines. Recombinant vaccine efficacy was tested in a murine model of pneumococcal pneumonia; ability to protect against invasive disease was compared to that of Prevnar13. This study provides the first proof of principle that protein polysaccharide conjugate vaccines produced in E. coli can be used to prevent pneumococcal infection. Vaccines produced in this manner may provide a low-cost alternative to the current vaccine production methodology.